Development of a touchscreen based slate device with Java application - Hamid, Tamanna; Adnan, Sakib Muhammad Muntasir; Nazneen, Shamama; Chowdhury, Zannatun Nayeem (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.